In Vitro Fecal Fermentation of High Pressure-Treated Fruit Peels Used as Dietary Fiber Sources - Viridiana Tejada-Ortigoza; Luis Eduardo Garcia-Amezquita; Ahmad E. Kazem; Osvaldo H. Campanella; M. Pilar Cano; Bruce R. Hamaker; Sergio O. Serna-Saldívar; Jorge Welti-Chanes (Molecules, 2019)
Fruit by-products are being investigated as non-conventional alternative sources of dietary fiber (DF). High hydrostatic pressure (HHP) treatments have been used to modify DF content as well as its technological and physiological functionality. Orange, mango and prickly pear peels untreated (OU, MU and PPU) and HHP-treated at 600 MPa (OP/55 °C and 20 min, MP/22 °C and 10 min, PPP/55 °C and 10 min) were evaluated. Untreated and treated fruit peels were subjected to fecal in vitro fermentations. The neutral sugar composition and linkage glycosidic positions were related to the production of short chain fatty acids (SCFA) resulting from the fermentation of the materials. After HHP-treatments, changes from multibranched sugars to linear sugars were observed. After 24 h of fermentation, OP yielded the highest amount of SCFA followed by PPU and MP (389.4, 282.0 and 204.6 μmol/10 mg DF, respectively). HHP treatment increased the SCFA concentration of orange and mango peel by 7 and 10.3% respectively, compared with the untreated samples after 24 h of fermentation. The results presented herein suggest that fruit peels could be used as good fermentable fiber sources, because they yielded high amounts of SCFA during in vitro fermentations.